Islamic Financial Management Student Skill Development Training in Developing a Profit and Loss Information System - Mashudi Mashudi; Nadia Roosmalita Sari (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Students of the Sharia Financial Management Study Program still use the manual calculation method in financial management, such as bookkeeping. This model is less effective when used in financial management because students have to think about entering several formulas to produce output in each calculation operation. This will be done repeatedly by students. This method will make students bored and even reduce the level of concentration in the learning process. The use of the internet as a means of supporting learning on campus is still not optimal because once again learning in this course uses conventional methods. The purpose of the service is to provide education about the importance of financial management by utilizing internet-connected technology and providing additional skills to students through training in developing a website-based financial management information system. The service implementation method used is by briefing on the importance of information systems for financial management as well as practices in developing simple information systems. The result of this activity is students are able to develop a simple information system such as for profit and loss calculation system.